2019
DOI: 10.3390/molecules24142661
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal-Induced Antibacterial Activity of Gold Nanorods Loaded into Polymeric Hydrogel against Pseudomonas aeruginosa Biofilm

Abstract: In this study, the photothermal-induced bactericidal activity of phospholipid-decorated gold nanorods (DSPE-AuNR) suspension against Pseudomonas aeruginosa planktonic and biofilm cultures was investigated. We found that the treatment of planktonic culture of Pseudomonas aeruginosa with DSPE-AuNR suspension (0.25–0.03 nM) followed by a continuous laser beam exposure resulted in ~6 log cycle reduction of the bacterial viable count in comparison to the control. The percentage reduction of Pseudomonas aeruginosa b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 72 publications
2
50
0
1
Order By: Relevance
“…В тех случаях, когда контакт клеточной стенки и НЧ влечет за собой необратимые разрушения (действие активных форм кислорода (АФК), повреждения при миграции энергии при плазмонном резонансе), более выраженный эффект достигается наличием развитой поверхности [41][42][43]. При фотодинамической или фототермической терапии с использованием инфракрасного лазерного излучения предпочтительно использовать НЧ с настраиваемым плазмонным резонансом в окне прозрачности тканей при 750−900 nm, и первым выбором в этом случае являются наностержни [44,45]. В нашем случае именно настройка плазмонного резонанса на длину волны излучения лазера сыграла свою роль в более эффективном действии наностержней по сравнению с нанокубиками (рис.…”
Section: Discussionunclassified
“…В тех случаях, когда контакт клеточной стенки и НЧ влечет за собой необратимые разрушения (действие активных форм кислорода (АФК), повреждения при миграции энергии при плазмонном резонансе), более выраженный эффект достигается наличием развитой поверхности [41][42][43]. При фотодинамической или фототермической терапии с использованием инфракрасного лазерного излучения предпочтительно использовать НЧ с настраиваемым плазмонным резонансом в окне прозрачности тканей при 750−900 nm, и первым выбором в этом случае являются наностержни [44,45]. В нашем случае именно настройка плазмонного резонанса на длину волны излучения лазера сыграла свою роль в более эффективном действии наностержней по сравнению с нанокубиками (рис.…”
Section: Discussionunclassified
“…The authors found that the fabricated nanocomposite showed pronounced antimicrobial activity against tested pathogenic microorganisms with limited cytotoxicity. In another recent publication, the photothermal effect of phospholipid-coated gold nanorods loaded into a poloxamer 407 hydrogel resulted in ≈4.5-5 log cycle reduction in the viable counts of a P. aeruginosa biofilm in comparison to the control sample [55]. The authors did not discern a difference in bacteria eradication with respect to the laser irradiation modality (continuous or pulsed).…”
Section: Polymeric Nanocomposites Containing Photothermally Active Gomentioning
confidence: 90%
“…The gold nanoparticle aggregation induced a change in the observed LSPR band, increasing both the NIR absorption and the photothermal conversion, which allowed for the elimination of Gram-positive bacteria. In another recent work, the photothermal-triggered effect of phospholipid-coated gold nanorods against P. aeruginosa planktonic and biofilm cultures was studied [55]. The authors found that the interaction between a planktonic culture of P. aeruginosa and a nanoparticle suspension, under NIR light exposure, resulted in a ≈6 log cycle reduction in the bacterial viable count with respect to the control.…”
Section: Plasmonic Gold Nanoparticles For Bacteria and Biofilm Phototmentioning
confidence: 99%
“…The necrotic cell death stimulates inflammatory responses which may usually compromise the antitumor activity (Pérez-Hernández et al, 2015). PTT is used for both tumor removal (Yang et al, 2010;Robinson et al, 2011;Tu et al, 2014;Wang et al, 2015) and bacterial disinfection in various types of bacteria Al-Bakri and Mahmoud, 2019;Qing et al, 2019).…”
Section: Introductionmentioning
confidence: 99%